Use of loop-mediated isothermal amplification (LAMP) for direct detection of mycobacterium in sputum. - Adhikari, Bal Ram (2007)
ABSTRACT: Most first line anti-tuberculosis drugs have less invitro activity against Mycobacterium avium, Mycobacterium intracellular and Mycobacterium kansasii. Therefore rapid species identification and proper use of drugs are key requirements for the effective treatment of tuberculosis as well as Mycobacterium avium complex-pulmonary disease (MAC-PD) and Mycobacterium kansasii-pulmonary disease (MK-PD). The development and evaluation of new diagnostic technique, which can identify the etiological agent in rapid way, is the This study was carried out from October 2005 to September 2006 based at Central Department of Microbiology (CDMTU), German Nepal Tuberculosis Project (GENETUP) and EICRC in collaboration with Osaka Perfectural Institute of Public Health, Japan. A total of 190( 129 from 43 new suspected pulmonary tuberculosis patients and 61 from 61follow of patients) sputum samples were collected in this study. All these samples were further processed for flurochrome staining but only 130(69 from new suspected pulmonary tuberculosis patients and 61 from follow up patients) sputum specimens were subjected to culture and LAMP. Thus 130 sputum specimens were included in this study to compare them with microscopy, culture and LAMP. Among them 54(41.54%) were found to be positive by flurochrome staining. Similarly 71(54.62%) Samples were positive by culture on L-J medium. Out of 130 sputum specimens, 78(60%) sputum specimens were positive by LAMP. Out of 78(100%) total LAMP positive cases, 76(97.44%) were positive with M. tuberculosis primer and remaining 2(2.56%) were positive with M. intracellular primer. None of the M. avium and M. kansasii cases were found from the samples that were included in this study. While 98.14% and specificity 67.11% while compare with microscopy. Therefore, LAMP is sensitive and specific molecular technique, which can used effectively for the diagnosis of clinically, microscopically, and culturally confusing cases, thus facilitating the effective treatment and case management of tuberculosis and other atypical mycobacterial infection. Due to its comparing the LAMP results with gold standard culture, the sensitivity, specificity, predictive value of negative test, percentage of false negative and percentage of false positive of LAMP were found to be 94.36%, 81.36%, 85.90%, 92.31%, 5.36% and 18.64% respectively. Similarly, LAMP had sensitivity easy operation and rapid amplification efficiency, it can be used in well-equipped laboratories for clinical use if sample preparation, nucleic acid extraction and cross-contamination controls are addressed. Key words : M. tuberculosis, M avium complex, M. kansasii, LAMP, TB, MAC-PD, MK-PD, Sputum